4(7x-44)=3-2(x+6)

Simple and best practice solution for 4(7x-44)=3-2(x+6) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(7x-44)=3-2(x+6) equation:


Simplifying
4(7x + -44) = 3 + -2(x + 6)

Reorder the terms:
4(-44 + 7x) = 3 + -2(x + 6)
(-44 * 4 + 7x * 4) = 3 + -2(x + 6)
(-176 + 28x) = 3 + -2(x + 6)

Reorder the terms:
-176 + 28x = 3 + -2(6 + x)
-176 + 28x = 3 + (6 * -2 + x * -2)
-176 + 28x = 3 + (-12 + -2x)

Combine like terms: 3 + -12 = -9
-176 + 28x = -9 + -2x

Solving
-176 + 28x = -9 + -2x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '2x' to each side of the equation.
-176 + 28x + 2x = -9 + -2x + 2x

Combine like terms: 28x + 2x = 30x
-176 + 30x = -9 + -2x + 2x

Combine like terms: -2x + 2x = 0
-176 + 30x = -9 + 0
-176 + 30x = -9

Add '176' to each side of the equation.
-176 + 176 + 30x = -9 + 176

Combine like terms: -176 + 176 = 0
0 + 30x = -9 + 176
30x = -9 + 176

Combine like terms: -9 + 176 = 167
30x = 167

Divide each side by '30'.
x = 5.566666667

Simplifying
x = 5.566666667

See similar equations:

| 24x-16=3x-2 | | x=-6dlope | | 2n+1+2n+3=52 | | b+5+7b+5=98 | | 5w^2+2=11w | | 2x-3yi+9=-x+2yi+5i | | 156+84= | | 5y+15=45 | | 2(2x+1)-(x+1)=5x-16 | | -70+-35x=-245 | | solvew^2-2w+1=0 | | 3*2=-2(-5)-4 | | 5*2=3(-5)+20 | | 3x-12-5x-10= | | 36+6X=34-4X | | -4=6x+7x+9 | | 8*(2p-4)*3p=20 | | 6x+1+5x=-65 | | a+10=b+2 | | 1+2x=x-2-4x | | -2x-5y=-27 | | 14(d+30)=-196 | | -4+4x-5x=-14 | | 3f=(2f+8) | | 6X-12+4X-1=-X+12-3X+5 | | x+(x+10)+2x=98 | | 4x+3=x+x+29 | | 2t-1=2t-5 | | 4y+3=y+21 | | 4y+3=y+22 | | 625-25x=0 | | (35x+67y)+(-20x+41y)= |

Equations solver categories